Актуальні проблеми українознавства - Міжрегіональна Академія управління персоналом (My University, 2012)
Розкриваються історичні, теоретичні та методологічні аспекти українознавчої дисципліни не тільки як складової духовності українства, а й як феноменального явища світової цивілізації. Проаналізовано роль і місце науки українознавства у розбудові демократичного суспільства суверенної європейської держави України. The historical, theoretical and methodological aspects of the Ukrainian studies discipline are revealed not only as a component of the spirituality of Ukrainians, but also as a phenomenal phenomenon of world civilization. The role and place of the science of Ukrainian studies in the development of a democratic society of the sovereign European state of Ukraine are analyzed.